2020
DOI: 10.2147/jpr.s207620
|View full text |Cite
|
Sign up to set email alerts
|

<p>Menstrual-Related Headaches Among a Cohort of African Adolescent Girls</p>

Abstract: Introduction: Migraine attacks associated with menstruation are generally perceived as more severe than attacks outside this period. Aim and Objective: The study aimed at determining the frequency of menstrual-related headaches among a cohort of senior secondary school girls in Abeokuta, Nigeria. We also determined its burden among these school girls. Methodology: This study was cross-sectional using a validated adolescent headache survey questionnaire. A self-administration of the instrument was done during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 23 publications
1
12
1
Order By: Relevance
“…Headache was reported more frequently in girls than in boys in 13 studies where a split according to sex was available 3,18,20,22–30,33 . Indeed, in female‐only studies, the prevalence rates were higher than in the mixed‐sex studies, ranging from 67.2% to 87.7% 16,17 . There was no difference in headache prevalence between different socioeconomic groups 3,24 …”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Headache was reported more frequently in girls than in boys in 13 studies where a split according to sex was available 3,18,20,22–30,33 . Indeed, in female‐only studies, the prevalence rates were higher than in the mixed‐sex studies, ranging from 67.2% to 87.7% 16,17 . There was no difference in headache prevalence between different socioeconomic groups 3,24 …”
Section: Resultsmentioning
confidence: 96%
“…In the study by Lima et al 17 , a need for pain medication was reported by 70.3% of adolescents (female‐only study), although only 26.2% sought medical attention, indicating that most subjects self‐medicated. Adebayo et al 16 noted that females with menstruation‐related headaches were significantly more likely to consult a doctor (53.8% vs 30.9%; p = 0.03) and were more likely to self‐medicate (76.9% vs 59.1%; not significant) compared with females with nonmenstruation‐related headaches. They also found that the most used medication was paracetamol (67.5% for all primary headaches).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations